Progress and recommendations in data ethics governance: a transnational analysis based on data ethics frameworks - Yanrui Qiu; Zhimin Hu (Humanities & Social Sciences Communications)
Abstract Human society has entered a new stage of development driven by data, where data is gradually becoming a factor of production. Big data and artificial intelligence technologies driven by data are changing the ways of global academic research, social governance, and economic development. In the era of big data, the frequent occurrence of data ethics violations has prompted countries to promote policies in the field of data ethics and to build relatively mature frameworks for data ethics. This study aims to sort out the progress of international data ethics frameworks through online research methods, literature surveys, and content analysis, summarizing the ethical regulations in the rapid development of big data and artificial intelligence. The study employs literature retrieval and search engine retrieval to select ten leading countries or supranational alliances in data and artificial intelligence development and their representative data ethics framework documents for in-depth research, including the United Kingdom (UK), the United States (US), Germany, Australia, Switzerland, Singapore, China, the European Union (EU), the United Nations Educational, Scientific and Cultural Organization (UNESCO), and the Organization for Economic Cooperation and Development (OECD). The study finds that while the specific content of data ethics principles varies among countries, there is a universality in underlying values, with data security and privacy protection comprising the core elements of data ethics governance. Data ethics frameworks in various countries present a synergistic governance model combining legal support, ethical guidance, and regulatory mechanisms, and have included extensive participation from interdisciplinary teams and stakeholders. It is recommended that countries, when improving their data ethics governance systems, integrate their national cultural characteristics based on universal values, draw on wisdom from various academic fields, balance the demands of different stakeholders, and adopt a governance model of legal support—ethical guidance—and regulatory mechanisms, applying diversified governance tools to achieve multi-level collaborative governance.